2017
DOI: 10.1155/2017/9685685
|View full text |Cite
|
Sign up to set email alerts
|

Total Ionizing Dose Effects of Si Vertical Diffused MOSFET with SiO2 and Si3N4/SiO2 Gate Dielectrics

Abstract: The total ionizing dose irradiation effects are investigated in Si vertical diffused MOSFETs (VDMOSs) with different gate dielectrics including single SiO 2 layer and double Si 3 N 4 /SiO 2 layer. Radiation-induced holes trapping is greater for single SiO 2 layer than for double Si 3 N 4 /SiO 2 layer. Dielectric oxidation temperature dependent TID effects are also studied. Holes trapping induced negative threshold voltage shift is smaller for SiO 2 at lower oxidation temperature. Gate bias during irradiation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Under the off state, the drain-gate terminal of the depletion-mode GaN HEMT and the source-drain channel of silicon MOSFET is the main current-leakage paths. Previous reports [14][15][16] showed that N-channel MOSFET is very sensitive to TID and that the drain current increases with the accumulated gamma-ray dose. In addition, the defect caused by neutron irradiation in the silicon layer and Si-SiO 2 interface could lead to an increase in the channel resistance and a decrease in the carriers' mobility in the MOSFET device.…”
Section: Discussionmentioning
confidence: 99%
“…Under the off state, the drain-gate terminal of the depletion-mode GaN HEMT and the source-drain channel of silicon MOSFET is the main current-leakage paths. Previous reports [14][15][16] showed that N-channel MOSFET is very sensitive to TID and that the drain current increases with the accumulated gamma-ray dose. In addition, the defect caused by neutron irradiation in the silicon layer and Si-SiO 2 interface could lead to an increase in the channel resistance and a decrease in the carriers' mobility in the MOSFET device.…”
Section: Discussionmentioning
confidence: 99%